Coal Characterization of Mallawa Formation in Mallawa Area, Maros Regency, South Sulawesi Province - Anshariah; Anwar, Habibie (Journal of Geology and Exploration, 2025)
Coal characterization is very heterogeneous chemically and physically, even within one seam there can be significant differences. Although some areas have coal, the characteristics of coal in one area are not necessarily the same as coal in other areas. This research was conducted to determine the coal rank based on calorific value, coal grade and coal characteristics of Mallawa Formation. This research was conducted using field data collection methods directly in the field in the form of coal samples, outcrop geometry data which were then subjected to laboratory analysis in the form of proximate, sulfur and caloric tests, and analyzing the relationship between total sulfur content in coal and coal ash content. The results showed that the coal rank based on coal calorles is in sub bituminous (low rank), coal grade in very low grade coal, with an average moisture content of 7.78%, average ash content of 39.99%, volatile matter 32.85% and average fixed carbon 19.39 cal/gr, and has a high sulfur content of 2,13%. There is a strong relationship between ash and sulfur content in coal with an R²value of 0 8238.